1998
DOI: 10.1021/la9801007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Critical Phenomenon of Hybrid Surfactant As Revealed by Viscosity Measurements

Abstract: We have recently found that sodium 1-oxo-1-[4-(tridecafluorohexyl)phenyl]-2-hexanesulfonate (FC6-HC4), one of the synthesized hybrid surfactants that have both fluorocarbon chain and hydrocarbon chain in the molecule, exhibits a thermoresponsive viscoelastic behavior in aqueous solution. The aim of this study is to examine the viscosity behavior in solution of synthesized surfactants with different chemical structures (different lengths of fluorocarbon and hydrocarbon chains) as a function of temperature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…FmPHnS are expected to be a good emulsifier for making aqueous fluorocarbon paints because they are able to emulsify fluorocarbon/water/hydrocarbon systems (6). The present authors have also reported that the synthesized hybrid surfactants form long-life micelles detected by NMR (7) and abnormally highly viscous solutions at about 10 wt% and 36 (8)(9)(10)(11)(12), and have a human tooth reformability for the prevention of its decay (13). These properties are characteristic of the hybrid surfactants and cannot be developed by mixed systems of fluorocarbon and hydrocarbon surfactants.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…FmPHnS are expected to be a good emulsifier for making aqueous fluorocarbon paints because they are able to emulsify fluorocarbon/water/hydrocarbon systems (6). The present authors have also reported that the synthesized hybrid surfactants form long-life micelles detected by NMR (7) and abnormally highly viscous solutions at about 10 wt% and 36 (8)(9)(10)(11)(12), and have a human tooth reformability for the prevention of its decay (13). These properties are characteristic of the hybrid surfactants and cannot be developed by mixed systems of fluorocarbon and hydrocarbon surfactants.…”
supporting
confidence: 55%
“…We have reported a peculiar viscosity behavior of highly concentrated aqueous solutions of the hybrid surfactants (8)(9)(10)(11)(12). Figure 6 shows typical photographs of 1, 5, 10, and 20 wt% solutions of F8EH3OS at 25 .…”
Section: Solution Properties Of Fmehnos At High Concentrationsmentioning
confidence: 99%
“…The surface properties critical micelle concentration CMC , effectiveness of surface tension reduction g CMC , efficiency of surface tension reduction pC 20 Fig. 5a .…”
Section: Surface Tension Measurementsmentioning
confidence: 99%
“…Yoshino et al [54] synthesized the fluoro-hybrid anionic surfactant FC6-HC4 by reacting l-[4-(perfluoroalkyl)phenyl]-l-alkanones with a sulphur trioxide/1,4-dioxane complex in 1,2-dichloroethane, followed by neutralization with aqueous sodium hydroxide, and then investigated its rheological behaviour as a function of temperature [6,54]. A thermo-thickening response was detected for concentrations ranging from 7 to 15 wt%; the viscosity peak and corresponding temperature could be tuned by varying surfactant concentration [6].…”
Section: Thermo-thickening Hybrid Wlmsmentioning
confidence: 99%